The Dynamics of Tax Avoidance: Examining How Profitability, Solvency, Capital Intensity, and Company Size Interact - Yulianti, Vista; Sulistyorini Wulandari, Dian; Yulianti, Yayang (PT. Banjarese Pacific Indonesia, 2024)
Tax avoidance represents a strategic maneuver by taxpayers to minimize their tax burden by capitalizing on the intricacies of tax legislation. This complex phenomenon encompasses a range of tactics, including leveraging exemptions, deductions, tax incentives, non-taxable income, deferring tax liabilities, and, regrettably, engaging in unethical practices such as bribery and forgery. This study seeks to unravel the intricate relationships between profitability, solvency, capital intensity, and company size regarding tax avoidance within the manufacturing sector, specifically targeting food and beverage firms listed on the Indonesia Stock Exchange from 2017 to 2022. Employing the Cash Effective Tax Rate (CETR) as a proxy for tax avoidance, we meticulously selected a sample of 70 companies through purposive sampling based on rigorous criteria. Our analysis, conducted via multiple linear regression using SPSS 25, reveals compelling insights: profitability, solvency, and capital intensity significantly bolster tax avoidance strategies, while larger company size appears to dampen these efforts. Collectively, these factors create a multifaceted influence on tax avoidance behaviors, highlighting the intricate dynamics at play within the corporate landscape.